2007
DOI: 10.1016/j.ijgo.2007.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate office endometrial sample requires further evaluation in women with postmenopausal bleeding and abnormal ultrasound results

Abstract: In women with postmenopausal bleeding and a nonreassuring transvaginal ultrasound evaluation, a nondiagnostic office endometrial sample does not rule out endometrial cancer and further endometrial sampling is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 24 publications
(47 reference statements)
3
48
0
Order By: Relevance
“…Our study results also showed a low concordance rate of 39.3% between EM aspiration and D&C biopsy conducted for follow-up evaluation of hormonal therapy and that 46.4% of the samples obtained by using the EM sampling method were insufficient. Van Doorn et al [29] conducted a prospective cohort study in 913 postmenopausal women with vaginal bleeding. Of these patients, 403 underwent office EM sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study results also showed a low concordance rate of 39.3% between EM aspiration and D&C biopsy conducted for follow-up evaluation of hormonal therapy and that 46.4% of the samples obtained by using the EM sampling method were insufficient. Van Doorn et al [29] conducted a prospective cohort study in 913 postmenopausal women with vaginal bleeding. Of these patients, 403 underwent office EM sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-six samples (16.4%) were insufficient. The authors also reported that three patients were diagnosed with EC and one patient was diagnosed with EM atypical hyperplasia when evaluated by using hysteroscopy and D&C biopsy [29]. Furthermore, Clark et al [30] reported that 20% of samples collected from postmenopausal women through EM aspiration biopsy contained insufficient materials.…”
Section: Discussionmentioning
confidence: 99%
“…These were caused by sampling error due to necrosis, and resulted in a diagnosis of EC upon reexamination. In cases of inadequate sampling and a suspicious EM thickness, further diagnostic workup is necessary or approximately 6% of EM pathology will be overlooked [14,15] . However, a recent systematic review of published studies found that a mean EM thickness of 2.9 mm in 2,952 postmenopausal women required histological examination and identified no valid cutoff value on which to base recommendations for EM histological examination in asymptomatic women [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies confirmed a high failure rate (51% and 64%, of which 30% and 48% were insufficient samples) [17,18]. Malignancy cannot be excluded in women with insufficient ES [19,20], and HY is often added. Insufficient ES is costly and painful for patients, and the wait time can cause anxiety.…”
Section: Discussmentioning
confidence: 92%